United Nations and Challenges of Resettlement and Reintegration of IDP’s in South Sudan, 2011-2018 - Iwuoha, Victor Chidubem; Nwagu, Clifford (ESUT JOURNAL OF SOCIAL SCIENCES, 2019)
The plight of Internally Displaced Persons (IDPs) in South Sudan has in recent years become a formidable problem of global significance and implications. Resettlement and reintegration of IDPs and refugees, and their sustainable livelihoods pose serious problems. The data collection and analysis were based on qualitative descriptive method. The paper argues that high levels of human and livelihood insecurity occasioned by incomprehensive disarming of rebels continue to undermine the safety and adequate reintegration and resettlement of IDPs and returning refugees in South Sudan. The Disarmament, Demobilization and Reintegration (DDR) programme in general and implementation of the reintegration components in particular had not made any headway. There was implementation of DDR in near-total isolation from other conflict resolution mechanisms such as reduction of small and light weapons, peace building, human development, and stabilization initiatives in the country. Again, capacities of local government and civil society to provide effective and equitable support to the ex-combatants and communities are insufficient. Therefore, a comprehensive UN disarmament programme should inculcate other international partners in order to ensure that ex-combatants and all rebel groups are absolutely disarmed, demobilized and effectively reintegrated with their livelihoods revived.